The elderly : contemporary issues - Sattar, M. A.; Kabir, M. (Mohammad); Bangladesh Association of Gerontology (Dhaka : Bangladesh Association of Gerontology, 2003)
Contributed articles, with reference to Bangladesh.
Some articles in Bengali.
Includes bibliographical references and index.
Keywords: Older people -- Bangladesh -- Social conditions; Older people -- Bangladesh -- Economic conditions; Older people -- Health and hygiene -- Bangladesh